2019
DOI: 10.3390/jmse7080249
|View full text |Cite
|
Sign up to set email alerts
|

What about Marine Renewable Energies in Spain?

Abstract: Renewable energies play a fundamental role within the current political and social framework for minimizing the impacts of climate change. The ocean has a vast potential for generating energy and therefore, the marine renewable energies are included in the Sustainable Development Goals (SDGs). These energies include wave, tidal, marine currents, ocean thermal, and osmotic. Moreover, it can also be included wind, solar, geothermal and biomass powers, which their main use is onshore, but in the near future their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…In 2016, it overtook coal as the second-largest form of generation capacity in Europe, only being overpassed by gas, and showing the highest development rate of every source considered [3]. Although the offshore wind energy sector is still far from the stage of maturity of its older brother (onshore wind) [4], the similarities between both have allowed offshore wind turbines [5] to become efficient and commercial-ready in a relatively short time [6]. During 2018, a total of 4496 MW were installed in six different countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, it overtook coal as the second-largest form of generation capacity in Europe, only being overpassed by gas, and showing the highest development rate of every source considered [3]. Although the offshore wind energy sector is still far from the stage of maturity of its older brother (onshore wind) [4], the similarities between both have allowed offshore wind turbines [5] to become efficient and commercial-ready in a relatively short time [6]. During 2018, a total of 4496 MW were installed in six different countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to onshore wind and photovoltaic technologies, currently with a very high rate of power installation, the IP has a large potential for the development of offshore technologies, due to the great length of its coasts [5][6][7]. Offshore wind energy has certain advantages over traditional onshore wind energy, such as an increased capacity factor (CF) or the higher availability of new areas for the development of future wind farms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It showed that the north coast of Spain (Galicia, Asturias, and Basque Country) is the area with the greatest potential, with 13 kW/m during the summer period and 70 kW/m during the winter (see Figure 2). In addition, the most interesting areas for harnessing the wave resource power are the Galician coast, as it represents the area with the greatest potential in Spain, with maximum values above 35 kW/m, and the Cantabrian coast, with an average of maximum values around 30 kW/m [4,5]. Given the previously described situation, the construction of a wave facility in the north coast of Spain is proposed, taking advantage of the wave energy converters that are currently available on the market and best addresses the coastal needs and characteristics.…”
Section: Introductionmentioning
confidence: 99%